La transformation de la relation sociale à l’énergie du fordisme au capitalisme néolibéral - Louison Cahen-Fourot; Cédric Durand (Revue de la Régulation)
In this contribution, we investigate the social relation to energy within the fordist accumulation regime and within the financialized and globalized capitalism that emerged in the 1970s. We aim at identifying shifts in the economy-energy nexus occurring alongside transformations in other fields. We analyse empirically and comparatively energy use in the main high income countries (France, Germany, Japan, United Kingdom, United States) from 1950 to 2010. Fordism is characterised by an extensive energy use and an intensive labour use. In particular, high labour productivity gains are fueled by a fast increase in energy quantity integrated into the production process. From 1970 onwards, a decrease in the growth of energy quantity goes together with a decrease in labour productivity growth and contributes to the erosion of the fordist social compromise. The emergence of neoliberalism entails a higher share of capital in income distribution and comes with a more and more intensive energy use, the productivity of which starts to increase noticeably, as well as with an increasing relocation of energy use.